Traumatic Atlantoaxial Rotatory Subluxation in Adult: Case Report - Alcântara, Rafaela Campos; Souza, Jacks Alan Tenório de; Joaquim, Andrei Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Traumatic atlantoaxial rotatory subluxation (AARS) is generally found in pediatric patients, rarely found in adults, being a life-threatening condition especially when early diagnosis is not possible, which can lead to severe late neurological deficits. We describe a 38-year-old patient, victim of physical aggression caused by strangulation attempt who developed AARS, an uncommon traumatic cause. During the hospital care, the early diagnosis allowed us to institute a conservative treatment, which made the case uncommon, since most of the time surgical treatment is imperative. With the patient awake and under analgesia, a closed reduction was performed that promoted immediate pain relief, followed by a prescription of wearing a Philadelphia-type collar for 8 weeks. During the follow-up, cervical spine radiographies demonstrated no subluxation after removing the cervical collar. The patient was asymptomatic after 6 months of treatment. This case supports the importance of nonoperative management of AARS in selected cases.
Keywords: atlantoaxial rotatory subluxation; trauma; adult